If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (x + -18) = x + -1(-2) Reorder the terms: 2x + (-18 + x) = x + -1(-2) Remove parenthesis around (-18 + x) 2x + -18 + x = x + -1(-2) Reorder the terms: -18 + 2x + x = x + -1(-2) Combine like terms: 2x + x = 3x -18 + 3x = x + -1(-2) Multiply -1 * -2 -18 + 3x = x + 2 Reorder the terms: -18 + 3x = 2 + x Solving -18 + 3x = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -18 + 3x + -1x = 2 + x + -1x Combine like terms: 3x + -1x = 2x -18 + 2x = 2 + x + -1x Combine like terms: x + -1x = 0 -18 + 2x = 2 + 0 -18 + 2x = 2 Add '18' to each side of the equation. -18 + 18 + 2x = 2 + 18 Combine like terms: -18 + 18 = 0 0 + 2x = 2 + 18 2x = 2 + 18 Combine like terms: 2 + 18 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| x/62=80 | | 2w+2l=68 | | y=225x+80 | | B=3x*4+3x*4 | | .3x=14 | | 1/x=5/9 | | y=7x+0.75 | | 1/×=5/9 | | -2x-15=12 | | n+34=17+34 | | A=4x+2x*8 | | 3w^2-108=0 | | (4+n)+9=4+(5+9) | | -8b-14+-5x=11 | | 3n+34+2n=-2+14n | | ((2n)-n)= | | 0.5(4x-9)=2x+8 | | 14/35=x/15 | | -16+46=-3(x+2) | | 5(2x+8)=-46+26 | | 0=5m-2n | | 4x-1/3=4/9 | | B+2b+3b-19+3b+10=360 | | 4+25x-40x+11=12x | | (3a+5)(2a-9)=0 | | 4s+2j=63 | | 4(n-6)-(5-7n)=10n | | 3*-9+2y=-15 | | F(-2)=17-(-2) | | 2j+4s=64 | | 6=-18b | | -3|2-5/4x|=18 |